2007
DOI: 10.1063/1.2746413
|View full text |Cite
|
Sign up to set email alerts
|

Micropumping of biofluids by alternating current electrothermal effects

Abstract: Electrokinetics is a preferred technique for microfluidic systems, but it is typically applied on fluids that are not too conductive ͑lower than 0.02 S / m͒, which excludes most biological applications. To solve this problem, this letter investigates microfluidic actuation by ac electrothermal ͑ACET͒ effect that was largely overlooked by the community. ACET originates from temperature gradients in the fluids, and it becomes more pronounced in more conductive fluids. This letter discusses two ACET pump designs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
130
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 5 publications
2
130
0
Order By: Relevance
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
“…Electrothermal fluid circulations can also take place in AC electrowetting when the frequency of the applied electric field is much greater than the typical frequency of electrode polarization [42,43]. Recently, electrothermal flow has been demonstrated to enhance microfluidic mixing [44] and immunoassays [45] and to pump biofluids [46,47] as well.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the high-conductivity fluid or cell culture medium, the layer of induced mobile charges becomes immensely compressed and loses its drag in the fluid. 32 ACET emerges from the interaction of an electric field with a temperature gradient and is especially suited for manipulating high conductivity fluids. 32 Although efficient ACET mixers were reported, several issues are remained to be addressed for the application in organs-on-a-chip systems.…”
Section: Introductionmentioning
confidence: 99%
“…32 ACET emerges from the interaction of an electric field with a temperature gradient and is especially suited for manipulating high conductivity fluids. 32 Although efficient ACET mixers were reported, several issues are remained to be addressed for the application in organs-on-a-chip systems. Ng et al 33 reported a micromixer that can be operated from the ACEO (r ¼ 1 mS/m) to the ACET (r ¼ 500 mS/m) with the voltage of 20 V. Sasaki et al 23 designed a pair of coplanar electrodes with a sinusoidal interelectrode gap to mix the fluids (r ¼ 1.29 S/m) with the voltage of 30 V. Wu et al 34 used ACET 3-D electrodes to mix the fluids (r ¼ 0.2-1 S/m) with the voltage of 42-51.75 V. The electric conductivity of cell culture medium is around 1.7 S/m, which is beyond the upper limit of the previous study of the ACET micromixer.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic pumps, on the other hand, do not require moving parts, and operate by converting kinetic sources into fluid momentum to drive flow. Common kinetic actuation methods include electrokinetic (EK), 15 magnetohydrodynamic, 16 electrochemical, 17 electrothermal, 18,19 and electrowetting. 20 EK flows are a popular class of low-volume, low-power micropumps, and can serve as a useful alternative to mechanical micropumps.…”
Section: Introductionmentioning
confidence: 99%